The impact of filter bed depth and solids loading using a multimedia filter - Ncube, Philani; Pidou, Marc; Jarvis, Peter (Taylor and Francis, 2018)
Design and operation of tertiary wastewater filters are not always well understood because of the inherent complexities of the wastewater matrix. Here, comparison of single, dual, triple and quadruple media (anthracite, flint, alumina and magnetite) filters were made to understand how the depth, media type and solids concentration influenced performance. The filter was improved by making the media deeper; however, the top 0.1 m of the filter retained the most solids. Additional layers of filter materials from single, dual, triple to quadruple improved the filter performance for the same depth of filter bed.
Keywords: Solids concentration; wastewater; depth filtration; multi-media; headloss